What contraception do women use after abortion? An analysis of 319, 385 cases from eight countries. Issue 1 (2nd January 2018) - Benson, Janie; Andersen, Kathryn; Brahmi, Dalia; Healy, Joan; Mark, Alice; Ajode, Achieng; Griffin, Risa
ABSTRACT: Contraception is an essential element of high-quality abortion care. However, women seeking abortion often leave health facilities without receiving contraceptive counselling or methods, increasing their risk of unintended pregnancy. This paper describes contraceptive uptake in 319, 385 women seeking abortion in 2326 public-sector health facilities in eight African and Asian countries from 2011 to 2013. Ministries of Health integrated contraceptive and abortion services, with technical assistance from Ipas, an international non-governmental organisation. Interventions included updating national guidelines, upgrading facilities, supplying contraceptive methods, and training providers. We conducted unadjusted and adjusted associations between facility level, client age, and gestational age and receipt of contraception at the time of abortion. Overall, postabortion contraceptive uptake was 73%. Factors contributing to uptake included care at a primary-level facility, having an induced abortion, first-trimester gestation, age ≥25, and use of vacuum aspiration for uterine evacuation. Uptake of long-acting, reversible contraception was low in most countries. These findings demonstrate high contraceptive uptake when it is delivered at the time of the abortion, a wide range of contraceptive commodities is available, and ongoing monitoring of services occurs. Improving availability of long-acting contraception, strengthening services in hospitals, and increasing access for young women are areas for improvement.